ANALISIS SEMANTIK MAKNA LEKSIKAL DAN GRAMATIKAL DALAM PUISI "DAN KEMATIAN MAKIN AKRAB" KARYA SUBAGIO SASTROWARDOYO - Sani, Wildan Nurul (JURNAL SELAKSA MAKNA, 2025)
This study does a full semantic analysis of the lexical and grammatical meanings in Subagio Sastrowardoyo's famous poem "Dan Kematian Makin Akrab." Using a method that combines descriptive linguistics and literary hermeneutics, the study carefully looks at how the poet's careful word choices create complex philosophical meanings. The analysis shows three main things: first, the strategic use of lexical items goes beyond their literal meanings to represent existential ideas; second, grammatical changes through affixation and syntactic structures create deep metaphorical meanings; and third, the balance between lexical precision and grammatical manipulation creates a unique poetic discourse that connects language and philosophical thought. The framework for the method incorporates qualitative textual analysis supported by theoretical perspectives from dynamic semantics (Cruse, 2000) and creative grammar (Pateda, 2010). This research contributes significantly to the interdisciplinary study of literature and linguistics by demonstrating how microscopic linguistic analysis can illuminate macroscopic philosophical themes in poetic works.   Penelitian ini menyajikan analisis semantik komprehensif terhadap makna leksikal dan gramatikal dalam puisi penting Subagio Sastrowardoyo "Dan Kematian Makin Akrab". Dengan pendekatan integratif yang memadukan linguistik deskriptif dan hermeneutika sastra, kajian ini mengkaji secara mendalam bagaimana pilihan linguistik penyair yang disengaja membangun makna filosofis berlapis. Analisis mengungkap tiga temuan fundamental: pertama, penggunaan strategis unsur leksikal melampaui makna denotatif untuk mewadahi konsep eksistensial; kedua, transformasi gramatikal melalui afiksasi dan struktur sintaksis menghasilkan pemaknaan metaforis yang mendalam; ketiga, interaksi antara presisi leksikal dan manipulasi gramatikal menciptakan wacana puitis unik yang menjembatani bahasa dan kontemplasi metafisik. Kerangka metodologis mencakup analisis teks kualitatif yang didukung perspektif teoretis dari semantik dinamis (Cruse, 2000) dan gramatika kreatif (Pateda, 2010). Penelitian ini memberikan kontribusi signifikan bagi kajian interdisipliner sastra dan linguistik dengan menunjukkan bagaimana analisis linguistik mikroskopis dapat menerangi tema filosofis makroskopis dalam karya puisi.